Uji Iritasi Formulasi Sediaan Krim Ekstrak Bawang Dayak (Eleutherine bulbosa (Mill.) Urb) pada Kelinci Albino Putih: Irritation Test of Bawang Dayak (Eleutherine bulbosa (Mill.) Urb) Extract Cream Formulation in White Albino Rabbits - Ardhany, Syahrida Dian; Effendie, Rizky Ramadhani; Novaryatiin, Susi (Jurnal Surya Medika (JSM), 2019)
Based on research before, ethanolic extract of bawang dayak (Eleutherine bulbosa (Mill.) Urb) has been tested can inhibit the growth of acne-causing bacteria, therefore made an anti-acne cream for easy used. Thi study aims to know primary irritation activity of bawang dayak using patch test method. The results showed that the primary irritation index of control group (0.625< 2), P1 was 1g of cream (0.75< 2), P2 was 0.5g of cream (0<2) and P3 was 0.25g of cream (0< 2) in category of invisible irritation, so it can be concluded that the cream of ethanolic extract of bawang dayak topically does not irritate animals.